Earthquake rupture variability along the central seismic gap segment (78°– 82°E) of the Himalayan Frontal Thrust, Western and Central Himalaya - Shreya Arora; Natalie Meenan; Eshaan Srivastava; Drew Cochran; Gurvinder Singh; Alana Williams; Mitthu Dhali; Monika Kumaiya; Ramon Arrowsmith; Javed N. Malik; Hisao Kondo (Scientific Reports)
Abstract Mapping the extents and terminations of surface ruptures is essential for a better seismic hazard assessment, as these factors indicate the magnitude and location of future earthquakes. The Himalayas and its active Himalayan Frontal Thrust (HFT) plate boundary, have experienced numerous damaging earthquakes in both recent and medieval times. The variability of the associated surface ruptures and the extent of the medieval earthquakes remain poorly understood. This study aims to improve the understanding of rupture extents and behavior along the ~ 650 km Central Seismic Gap (CSG) segment by analyzing paleoseismic trench data from sixteen previously published trenches, including new excavations during this study at Teliwara and Goujani. Evidence from Goujani suggests a penultimate event between calAD1437 and calAD1576 and Most Recent Earthquake (MRE) between calAD1662 and AD1894 with a minimum cumulative slip of at least 7 m. The Teliwara site reveals evidence of MRE occurring between calAD1665 and calAD1956 with a cumulative slip of 12.3 m. Integrating these findings with data from other paleoseismic sites allows for a detailed reconstruction of rupture patterns and timing along the CSG segment. Analysis of age probability density functions (PDFs) indicate three significant events: Earthquake 1 dated between calAD1320 and calAD1412, likely ruptured 259–360 km of the HFT. Earthquake 2, dated between calAD1437 and calAD1576, appears to have ruptured 490 km with rupture termination near the Faizabad Ridge, suggesting it was an asperity confined rupture. Earthquake 3 occurred between calAD1748 and calAD1894. These events correspond temporally to the 1344, 1505, and 1803 historical earthquakes, or to unrecorded events of similar age. Estimated moment magnitudes (Mw) for Earthquakes 1 and 2 are approximately 8.3–8.5 and 8.7, respectively. These findings suggest that the CSG segment has experienced large ruptures influenced by structural asperities.